Development Of Ethnopedagogy-Based Thematic Learning Modules For Elementary Students In The Independent Learning Curriculum - Tirtoni, Feri; Suwarta, Nyoman (Proceeding International Conference on Lesson Study, 2023)
Education in Indonesia plays an important role in building the nation. Educational Efforts to make humans become better individuals. Through this training, teachers can instill the noble values of the Indonesian people in students at the school. Ethnopedagogy, or what is commonly known as education based on regional wisdom, is the use of local areas for education. In addition to learning about local wisdom around them, students can understand the learning conveyed in thematic learning activities with the help of information technology, such as the internet. Thematic learning activities can be referred to as discussion activities. In this thematic learning, more emphasis is placed on learning by doing or the application of the concept of learning by doing, so the teacher must organize and plan learning in such a way that it becomes a meaningful experience for students. This research data collection technique is very important because this method is used as a strategy to collect necessary data. Data collection techniques used in this study were observation, in-depth interviews and documentation. It can be seen that the thematic ethnopedagogy has a good effect on the learning outcomes of fifth grade students who receive more points than the KKM. The application of etopedagogy in thematic learning besides having a good effect on students’ thematic learning outcomes, also has a good effect on students’ attitudes. Learning is in line with material from several subjects in one topic